Rice biotechnology and its potential to combat vitamin A deficiency: a case study of golden rice in Bangladesh - Roukayatou Zimmermann; Faruk Ahmed (University of Bonn, Center for Development Research (ZEF), 2006)
Vitamin A deficiency (VAD) remains a public health problem in many developingcountries. Thousands of preschool children go blind every year, and many of them die due toVAD. Also VAD weakens the immune system, making children to be prey to infection diseases. Adults are also affected by VAD, and the most affected population groups are pregnant and lactating women. Fortunately, there are many ways to tackle this problem, including pharmaceutical supplementation, food fortification, dietary education, and breeding food crops rich in micronutrient. One of the famous examples of crops rich in micronutrient is Golden Rice (GR). Golden Rice has been genetically engineered to produce beta-carotene in the grain endosperm. Beta-carotene is a precursor of vitamin A (VA). This study analyses the potential health impacts of this rice on VA deficient consumers in Bangladesh. We have calculated the current burden of VAD in the country by using the methodology of disability-adjusted life years (DALYs), then simulated the future benefits by using 24 hours recall data for individual food intake of household members. Finally, we have juxtaposed the health benefits and overall cost of Research and Development (R&D) of GR in Bangladesh to assess its cost-effectiveness. Since GR is still in the stage of R&D, our calculations are of ex ante nature. Therefore, we have used scenarios for our calculations. To test the robustness of parameters used, we have conducted a sensitivity analysis. The results of our study show that GR has a potential to reduce significantly the burden of VAD in Bangladesh and the technology is cost-effective. However, the same results show also that GR alone will not completely eliminate the problems of VAD; therefore GR should be seen as a complementary intervention to the existing ones. – – Vitamin A Mangel (VAM) bleibt ein schwerwiegendes Gesundheitsproblem in vielen Entwicklungsländern. Jedes Jahr erblinden tausende Kinder im Vorschulalter, und viele von ihnen sterben infolge von VAM. Die Mangelkrankheit schwächt das Immunsystem und macht Kinder anfällig für Infektionskrankheiten. Auch Erwachsene sind betroffen, insbesondere schwangere Frauen und stillende Mütter. Erfreulichweise gibt es Behandlungsmethoden, wie z.B. pharmazeutische Mittel, Nahrungsmittelergänzungen, Aufklärung zu einer ausgewogenen Ernährung und Grundnahrungsmittelpflanzen, die durch züchterische Eingriffe einen höheren Gehalt an Mikronährstoffen enthalten. Eines der bekanntesten Beispiele ist Golden Rice (GR). Dies ist ein Reis, der gentechnisch verändert wurde, um Betakarotin im Endosperm zu produzieren, welches der menschliche Körper in Vitamin A umwandeln kann. Die vorliegende Studie analysiert den potentiellen Einfluss des GR auf die von VAM Betroffenen in Bangladesh. Wir haben die aktuellen gesundheitlichen Schäden durch VAM in Bangladesh mit Hilfe der DALY (Disability-Adjusted Life Years) Methode berechnet und dann den zukünftigen Nutzen simuliert. Schließlich haben wir den so berechneten potentiellen gesundheitlichen Nutzen den Gesamtkosten aus Forschung und Entwicklung (F&E) gegenübergestellt, um die Kostenwirksamkeit von GR zu bewerten. Da sich der GR immer noch im F&E Stadium befindet, ist dies eine ex-ante Studie, bei der wir verschiedene Szenarien für unsere Berechnungen eingesetzt haben und durch eine Sensitivitätsanalyse die Robustheit der Parameter getestet haben. Das Ergebnis zeigt, dass GR das Potential hat, die Auswirkungen von VAM in Bangladesh signifikant und kosteneffektiv zu reduzieren. Es ist aber auch klar, dass GR die Probleme von VAM nicht vollständig beheben kann, sondern als komplementäres Instrument zu anderen Maßnahmen betrachtet werden sollte.
Keywords: 330